Strategi rantai nilai untuk keberlangsungan usaha industri rumah cokelat di Kota Palu - Gusman Sunding; Chalarce Totanan; Mustamin Aras; Rahayu Indriasari; Muhammad Ansar; Jurana Jurana (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2023)
The purpose of this study was to determine the strategic value chain for the sustainability of the Chocolate House Industry business in the city of Palu, which is located on Jalan Setia Budi, East Palu, Central Sulawesi. The number of respondents was 4 people consisting of 1 leader, 1 head of production and 2 employees. Data analysis technique uses descriptive qualitative.The value chain strategy at Rumah Coklat can be seen from the supporting (secondary) activities which include Infrastructure, HR Management, Technology Development and Procurement activities. Primary (primary) involvement includes raw material handling, production process, service and marketing. The Value Chain Strategy activities as a whole support each other to create chocolate products. The results of the assessment of the value chain strategy in the continuity of the Chocolate House Industry business are 3, namely: (1) Competitive advantage, namely by utilizing the original taste of the original cocoa beans, Utilizing the original cocoa butter as a raw material for making chocolate to give a distinctive taste from chocolate so that it is preferred the community, continue to maintain and improve product quality so that it becomes a superior product for the Palu city government. (2) Differentiation Strategy, namely by paying attention to the quality of the ingredients used and always maintaining the taste produced, (3) Cost advantage strategy, namely producing authentic chocolate from Central Sulawesi which is processed into chocolate with levels of 56 percent, 80 percent and 90 percent. Thus producing premium chocolate, not compound chocolate. The value chaos strategy all synergizes to shape, support and support the chocolate manufacturing process in order to gain margins/profits. Optimal margin provides the sustainability of the chocolate house industry in maintaining existence and maintaining business (Going Concern).